Ocean warming impairs the predator avoidance behaviour of elasmobranch embryos. Issue 1 (17th June 2021) - Ripley, Daniel M; De Giorgio, Sara; Gaffney, Kirstin; Thomas, Lowri; Shiels, Holly A
Abstract : Lay Summary Shark embryos use a freezing behaviour to avoid being detected by predators. Here, we show that the duration an individual can perform the freezing behaviour is reduced by ocean warming, potentially increasing the vulnerability of embryonic sharks to predation. Abstract: Embryogenesis is a vulnerable stage in elasmobranch development due in part to high predation mortality. Embryonic elasmobranchs respond to potential predators by displaying a freezing behaviour, characterized by the cessation of pharyngeal respiration followed immediately by coiling of the tail around the body. We hypothesized that the duration of this freeze response is limited by the embryo's requirement for oxygen. Here, Scyliorhinus canicula embryos were incubated at either 15°C or 20°C during embryogenesis and tested for the duration of, and metabolic consequence of, the freeze response at their respective incubation temperature. Freeze response duration was negatively impacted by routine metabolic rate; embryos at 20°C had 7-fold shorter freeze duration than those at 15°C, potentially increasing their susceptibility to predation. These data demonstrate the capacity for climate change stressors to affect animal behaviour and suggest that this may occur by eliciting changes in the organism's metabolism. We suggest altered predator avoidance behaviour is a new factor to consider when assessing the impact of climate change on the conservation and management of oviparous elasmobranch species.